2020
DOI: 10.1177/0300060520902912
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous transfusion of iron sucrose reduces blood transfusions and improves postoperative anaemia after a second thoracotomy: a propensity-score matching study

Abstract: Objective: To evaluate the efficacy of intravenous iron sucrose (IS) in the perioperative period of a second thoracotomy after open-heart surgery. Methods: This study enrolled patients that underwent a second thoracotomy after previous open-heart surgery. Propensity-score matching was used to match patients that received oral iron therapy with those that received IS after admission. The baseline demographic and clinical characteristics, perioperative data and adverse outcomes were compared between these two ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…avoids the gastrointestinal side effects and allows for more rapid correction of iron stores and anaemia. Luo et al [27] showed significant decreases in red blood cell transfusion and increases in Hgb following iron sucrose infusion in patients having repeat thoracotomy following cardiac surgery. In addition, Triphaus et al [28 ▪ ] showed that preoperative iron supplementation reduced red blood cell transfusion and hospital length of stay (LOS) in patients with IDA having major surgery compared with patients with IDA who were not treated with iron.…”
Section: Iron Deficiency Anaemiamentioning
confidence: 99%
“…avoids the gastrointestinal side effects and allows for more rapid correction of iron stores and anaemia. Luo et al [27] showed significant decreases in red blood cell transfusion and increases in Hgb following iron sucrose infusion in patients having repeat thoracotomy following cardiac surgery. In addition, Triphaus et al [28 ▪ ] showed that preoperative iron supplementation reduced red blood cell transfusion and hospital length of stay (LOS) in patients with IDA having major surgery compared with patients with IDA who were not treated with iron.…”
Section: Iron Deficiency Anaemiamentioning
confidence: 99%